ACCOUNTING STUDENTS PERCEPTION OF ETHICS PREPARATION TO THE FINANCIAL STATEMENTS - Sukirman Sukirman (JAKSTIK Journal, 2005)
This study aims to examine differences in perceptions of accounting students to ethicalfinancial statements, among students who already take a course in ethics education tostudents who have not take a course in ethics education. Analysis based on data from 134respondents via the research collection used by researchers kuesioner.Metode Mann Whitneytest was used to examine differences in perceptions of students towards the preparation offinancial reports and test students' responsibility over financial reporting, whereas the T-TestTest used to test differences in perception between men and wanita.Hasil research shows thatthere are significant differences between students who have taken ethics education to studentswho have not taken ethics education. Students who have taken ethics education has a goodperception of the ethical preparation of financial statements compared with students whohave not taken ethics education. As for responsibility in reporting of financial information ofstudents who have not taken ethics education are higher than the students who have not takenethics education. This means that the accounting curriculum at universities is considered notenough to give stock ethics to the students to plunge into the world of work.